(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Anti-vascular endothelial growth factor (VEGF) agents have been successfully used to reduce the incidence of perioperative and postoperative complications in patients with proliferative diabetic retinopathy (PDR). Purpose: To evaluate the efficacy of a modified staged method of surgical treatment for PDR which involves intravitreal aflibercept (IVA) injection 1-mg prior to vitrectomy. Material and Methods: This study involved 75 patients (75 eyes) with PDR. Group 1 (the control group) received vitrectomy only; Group 2, IVA 1.0 mg prior to vitrectomy; and Group 3, IVA 2.0 mg prior to vitrectomy. Results: Mean visual acuity at 2 months and 6 months was significantly better in eyes treated with aflibercept than in those not treated with aflibercept (p1-2 = 0.0001; p1-3 = 0.0001). In the early postoperative period, transient vitreous hemorrhage was observed significantly more frequently in the control group than in group 2 (p1-2 = 0.0003) or group 3 (p1-3 = 0.0004). The incidence of transient vitreous hemorrhage within 2 months after vitrectomy was also significantly higher in the control group than in group 2 (p1-2=0.09) or group 3 (p1-2=0.017). By 6 months after surgery, rubeosis developed in 5 eyes (16.1%) of the control group, and in no eye of the 44 eyes that received intravitreal aflibercept (р= 0.02). Conclusion: Our modified staged method of surgical treatment for PDR enabled an improvement in visual acuity at 2 months and 6 months after surgery; a reduction in the incidence of transient vitreous hemorrhage in the early postoperative period; and reduction in the risk of the development of iris rubeosis in the late period after surgery.